Parents under Stress - Evaluating Emergency Childcare Policies during the First Covid-19 Lockdown in Germany - Simone Schüller; Hannah S. Steinberg (Center for Economic Studies and Ifo Institute (CESifo), 2021)
What are the effects of school and daycare facility closures during the COVID-19 pandemic on parental well-being and parenting behavior? Can emergency childcare policies during a pandemic mitigate increases in parental stress and negative parenting behavior? To answer these questions, this study leverages cross-state variation in emergency childcare eligibility rules during the first COVID-19 lockdown in Germany and draws on unique data from the 2019 and 2020 waves of the German AID:A family panel. Employing a DDD and IV approach we identify medium-term ITT and LATE effects and find that while emergency care policies did not considerably affect parents' life satisfaction, partnership satisfaction or mental health, they have been effective in diminishing harsh parenting behavior. We find partly gendered effects, specifically on paternal parenting behavior. Our results suggest that decreasing parental well-being likely constitutes a general effect of the pandemic, whereas the observed increase in negative and potentially harmful parenting behavior is largely directly caused by school and daycare facility closures.
Keywords: D04; D13; I18; I31; J13; 330; parental well-being; harsh parenting; Covid-19; policy evaluation; school and daycare closures; AID:A; difference-in-difference-in-differences; instrumental variable estimation